Safety Leadership and Work Environment Management in Building Patient Safety Culture through Work Motivation - Dwi Meutia Julyta; Duta Liana; Nofierni Nofierni (Green Inflation: International Journal of Management and Strategic Business Leadership, 2026)
This study investigates the effects of safety leadership and work environment on patient safety culture, with work motivation as an intervening variable among nurses at Hospital X in Jakarta. A quantitative approach using a cross-sectional design was employed, with data collected from 111 nurses through structured questionnaires. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results show that safety leadership and work environment have significant positive impacts on nurses’ work motivation. Additionally, work motivation directly influences patient safety culture. The study also finds that work motivation partially mediates the relationship between safety leadership and patient safety culture, as well as between work environment and patient safety culture. These findings suggest that both leadership practices and environmental conditions affect patient safety culture directly and indirectly by enhancing nurses’ motivation. The study highlights the importance of safety leadership and supportive work environments in promoting a sustainable patient safety culture through improved nurse motivation. From a practical perspective, hospital management should focus on fostering effective safety leadership practices and creating conducive work environments to enhance patient safety culture. This research contributes to the literature on patient safety and management by providing empirical evidence on the role of work motivation in strengthening safety culture in hospitals.